Les Pseaumes de David - Calvin, Jean 1509-1564; Marot, Clément 1496-1544; Bèze, Théodore de 1519-1605 (Geneva [?] Estienne, 1568)
Originally published in 1551, the translations of 150 Psalms of David by Clement Marot (1496-1544) as completed by Theodore de Bèze (1519-1605, Calvin's successor as spiritual leader of the Republic of Geneva) were used almost exclusively by the Calvinists (Genevan Psalter). The psalter was the main medium of popular fervour among the Reformed. The Edict of Nantes forbade Reformed worship in towns where the King of France resided and the only town allowed around Paris was Charenton.
The Genevan psalter was originally published by Calvin in 1539. It was enhanced in 1543 by Clément Marot and Théodore de Bèze. This is the oldest version in the collection.
The Psalms are followed by The Form of Ecclesiastical Prayers, The Form of Administering Baptism, The Manner of Celebrating Holy Communion, The Catechism, and Daily Exercise of the Christian.
Mis en rime Françoise, par Clement Marot, & Theodore Beze
Keywords: 16th Century (1501-1600); Church music; Calvinism; Psalm; Poetry; Prayer; France